Chromobacterium violaceum Pathogenicity: Updates and Insights from Genome Sequencing of Novel Chromobacterium Species - Batista, Juliana H.; da Silva Neto, José F. (Frontiers in Microbiology, 2017)
Chromobacterium violaceum is an abundant component of the soil and water microbiota in tropical and subtropical regions around the world. For many years, it was mainly known as a producer of violacein and as a reporter for the discovery of quorum sensing molecules. However, C. violaceum has recently emerged as an important model of an environmental opportunistic pathogen. Its high virulence in human infections and a mouse infection model involves the possession of several predicted virulence traits, including two type III secretion systems (T3SSs). In this article, in addition to providing an update on the new clinical cases of human C. violaceum infections, we will focus on recent advances in understanding the molecular mechanisms regarding C. violaceum pathogenesis. It has been demonstrated that the C. violaceum Cpi-1 T3SS plays a pivotal role in interaction with host cells. It is required for the secretion of effector proteins and is the agonist recognized by the NLRC4 inflammasome from innate immune cells. Pyroptosis and its release of hepatocytes for killing by neutrophils are key events required for the clearance of C. violaceum. Given the prominent role of T3SSs in C. violaceum virulence, we examine their occurrence in the Chromobacterium genus, taking advantage of several draft genome sequences of Chromobacterium species that have recently become available. Our finding that the Cpi-1 T3SS is widespread among Chromobacterium species points toward the pathogenic potential of this genus for humans or to novel roles of the T3SS in the interaction of Chromobacterium species with other organisms.